2018
DOI: 10.2105/ajph.2017.304115
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Blood Lead Levels by Length of Time From Resettlement to Health Screening in Kentucky Refugee Children

Abstract: Elevated blood lead levels were reduced with increasing length of time of resettlement in unadjusted and adjusted models. Improved housing, early education, and effective safe-house inspections may be necessary to address EBLLs in refugees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A cross-sectional study of Greek children found BPb ≥5 µg/dL among 27.7% of migrants but only 1.2% of natives 18. Multiple cross-sectional analyses in the USA have identified that newcomer refugee children settling in Florida,33 Kentucky34 and New Hampshire14 were significantly more likely to have elevated BPb compared with native children. Additionally, a case–control study of 203 children matched on age, date of test and residential area in New York City found an elevated risk of lead poisoning in foreign-born children relative to US-born children (OR 10.9; 95% CI 3.3 to 36.5) 11…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of Greek children found BPb ≥5 µg/dL among 27.7% of migrants but only 1.2% of natives 18. Multiple cross-sectional analyses in the USA have identified that newcomer refugee children settling in Florida,33 Kentucky34 and New Hampshire14 were significantly more likely to have elevated BPb compared with native children. Additionally, a case–control study of 203 children matched on age, date of test and residential area in New York City found an elevated risk of lead poisoning in foreign-born children relative to US-born children (OR 10.9; 95% CI 3.3 to 36.5) 11…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, three issues that are related to lead exposure in LMICs deserve attention. First, a number of studies have documented elevated BLLs among refugees, either prior to or after settling in the U.S. [ 7 , 8 , 9 , 10 , 11 , 12 ]. These statistics underscore the fact that the global problem of lead can take on very local meaning outside of the countries of origin.…”
Section: Exposure Patternsmentioning
confidence: 99%
“…2 Subsequent reports have confirmed this health concern for refugee populations. [3][4][5][6][7][8] For example, an investigation by the Centers for Disease Control and Prevention (CDC), published in 2004, determined that African refugee children with histories of malnourishment who were resettled in New Hampshire were more susceptible to environmental lead exposure than US-born children living in the same housing development. 3 A 2011 report on Burmese refugee children resettled in Indiana showed a high prevalence of EBLLs that was associated with culturally traditional cosmetic use in the home.…”
mentioning
confidence: 99%
“…7 A 2018 study of refugee children resettled in Kentucky also showed that EBLLs were associated with older housing, and that although blood lead levels (BLLs) were initially high, they did decline in some refugees after resettlement in the United States. 8 Although CDC specifies that no amount of lead in the blood is safe or acceptable, historically it had defined EBLLs as being !10 mg/dL. Before 2012, however, research suggested that lower BLLs could cause irreversible harm to young children, particularly to their neurocognitive development.…”
mentioning
confidence: 99%
See 1 more Smart Citation